Olfactory bulb hypoplasia in Prokr2 null mice stems from defective neuronal progenitor migration and differentiation - Haydn M. Prosser; Allan Bradley; Maeve A. Caldwell (2007)
Abstract New neurons are added on a daily basis to the olfactory bulb (OB) of a mammal, and this phenomenon exists throughout its lifetime. These new cells are born in the subventricular zone and migrate to the OB via the rostral migratory stream (RMS). To examine the role of the prokineticin receptor 2 (Prokr2) in neurogenesis, we created a Prokr2 null mouse, and report a decrease in the volume of its OB and also a decrease in the number of bromodeoxyuridine (BrdU)‐positive cells. There is disrupted architecture of the OB, with the glomerular layer containing terminal dUTP nick‐end labeling (TUNEL) ‐positive nuclei and also a decrease in tyrosine hydroxylase‐positive neurons in this layer. In addition, there are increased numbers of doublecortin‐positive neuroblasts in the RMS and increased PSA‐NCAM (polysialylated form of the neural cell adhesion molecule) ‐positive neuronal progenitors around the olfactory ventricle, indicating their detachment from homotypic chains is compromised. Finally, in support of this, Prokr2‐deficient cells expanded in vitro as neurospheres are incapable of migrating towards a source of recombinant human prokineticin 2 (PROK2). Together, these findings suggest an important role for Prokr2 in OB neurogenesis.